Formation of Cost Management System of Oil and Gas Extraction Enterprises - Кафка, С. М.; Степанюк, О. С. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
In the face of growing challenges in Ukraine’s energy security the smooth operation of all elements in the cost management system of oil and gas companies is acquiring a particular importance for their effective work. Therefore, the system and elements of the cost management process at the enterprise, which are necessary for the formation of databases with the necessary information for the developing effective cost management options, have been investigated. It is established, that for the control of production costs, their detailing and grouping, the spots of expenses appearance are of crucial importance, so the development of accounting for these features determines today the main direction of the cost accounting improvement, control and management of the production costs formation. Three approaches to the cost management have been proposed (creation of working groups to solve particular cost problems, commission of the authorized persons on cost management, creation of "problem groups") that will allow to manage the costs solely on the basis of a comparison of material and financial flows that will make the results understandable for managers of all levels.